Investigating green initiatives at South African public universities - Tshivhase, Ms Lelo; Bisschoff, Christo Alfonzo (Nurture, 2024)
Purpose: All institutions of higher learning including public universities in South Africa must participate in green programmes in order to be considered socially responsible. This requires a better understanding of the green environment and green initiatives. Hence, the primary objective is to identify and investigate the existing green initiatives implemented at South African universities. Design/Methodology/Approach: The study investigated five key green initiatives: 1) Renewable energy generation and consumption. 2) Water-saving technology and consumption. 3) Waste management. 4) Sustainable buildings. 5) Personnel training and awareness creation. A five-point Likert scale collected data across 18 criteria measuring the five green initiatives. University managers completed and returned 149 questionnaires but only 144 were usable. Findings: The data has marginal reliability (α=0.412), acceptable sample adequacy (KMO=0.531) and significance at the 95% confidence level (p≤0.05). The results show that universities implement 20-25% of their green initiatives. The exploratory factor analysis identified seven factors explaining a cumulative variance of 56.14%. They are: 1) Recovering natural resources and recycling. 2) Supportive infrastructure. 3) Reallocation of resources. 4) Conservation of natural resources. 5) Leadership involvement and improved communication. 6) Improved technology.7) Efficient use of financial resources. Conclusion: This research contributes to the "going green at universities" of knowledge in South Africa. It is valuable to students, researchers, communities and the department of education in their pursuit to implement green initiatives at universities.